This Toxic Material: A Poetic (Re)Presentation of Cancer/Environment Assemblages. Issue 4 (February 2014) - Gullion, Jessica Smartt
In this project, I explore cancer/environment assemblages as situated in a geographic space identified as having excess cancer incidence. I draw on theories of vibrant materialism to draw interconnections between the cultural and natural experiences of cancer. Through in-depth interviews with cancer patients who attribute their cancer to an environmental cause, I seek to understand how they position themselves within the assemblage. I invite the reader to connect to this assemblage through a rhizome of poetic representation.